2021
DOI: 10.1186/s13018-021-02871-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intra-articular administration of adenosine, lidocaine and magnesium solution and tranexamic acid for alleviating postoperative inflammation and joint fibrosis in an experimental model of knee arthroplasty

Abstract: Background Dysregulated inflammatory responses are implicated in the pathogenesis of joint stiffness and arthrofibrosis following total knee arthroplasty (TKA). The purpose of this study was to compare the effects of intra-articular (IA) administration of tranexamic acid (TXA), an anti-fibrinolytic commonly used in TKA, and ALM chondroprotective solution on postoperative inflammation and joint tissue healing in a rat model of knee implant surgery. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Our model reflects these clinical observations as TKA was accompanied by elevated IL-6 and TNFα levels and functional deficits consistent with acute postoperative pain. Morris et al reported a similar pattern of elevated IL-6, though not to a significant degree, following knee surgery in rats [ 17 ]. The animals were observed initially limping and then gradually recovered normal gait, confirming that rats subjected to TKA regained normal knee loading and function.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our model reflects these clinical observations as TKA was accompanied by elevated IL-6 and TNFα levels and functional deficits consistent with acute postoperative pain. Morris et al reported a similar pattern of elevated IL-6, though not to a significant degree, following knee surgery in rats [ 17 ]. The animals were observed initially limping and then gradually recovered normal gait, confirming that rats subjected to TKA regained normal knee loading and function.…”
Section: Discussionmentioning
confidence: 93%
“…Elucidation of such pathways necessitates a preclinical TKA model that closely mimics the clinical procedure as well as outcomes including acute postoperative pain and recovery of function. While several TKA models have been reported in rats [14][15][16][17], none of these have demonstrated responsiveness to analgesia and complete restoration of knee function as reported in clinical studies. Herein, we describe a new preclinical model of TKA in rats that is accompanied by behaviors indicative of acute postoperative pain responsive to clinically employed analgesics, and exhibits functional recovery and pain resolution as observed in TKA patients.…”
Section: Introductionmentioning
confidence: 99%
“…From previous studies on ALM solution, it is known that small-volume ALM therapy has multiple protective effects on the whole organism, such as the improvement of the cardiac and hemodynamic function, correction of coagulopathy, reduction of inflammation, endothelial injury, and infection, as well as improvement of oxygenation [ 21 , 23 , 27 , 43 , 44 ]. Additionally, the antifibrotic and antiapoptotic effect of ALM therapy may explain the significantly higher strength on days 4 and 7 compared with the control groups [ 26 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…ALM solution demonstrated increased survival in hemorrhagic shock, cardioprotective effects, improved microvascular perfusion with concomitant improved oxygenation, and pulmoprotective and nephroprotective properties in small and large animal studies conducted to date [ 22 , 23 , 24 , 25 ]. Furthermore, Morris et al demonstrated less arthrofibrosis with ALM therapy in an animal model with total knee arthroplasty [ 26 ]. ALM therapy has also demonstrated reduced systemic inflammation, thrombocyte dysfunction, and coagulopathy after different trauma states [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“… 14 Interestingly, perioperative adenosine, lidocaine, and Mg 2+ (ALM) therapy was shown to dampen early systemic and local inflammation in both sexes following ACL rupture and surgical repair. 14 ALM therapy was chosen because of its ability to blunt inflammation and reduce immune dysfunction in experimental models of total knee arthroplasty, 20 , 21 hemorrhagic shock, traumatic brain injury, and sepsis. 22 The aim of the present study was to investigate the effects of perioperative ALM therapy on knee function, inflammation, and joint tissue repair in males and females at 28 days postoperatively.…”
Section: Introductionmentioning
confidence: 99%